Modelling monthly operation policy for the Mosul Dam, northern Iraq. (2015) - Al-Aqeeli, Yousif H.; AlMohseen, Kamel A.; Lee, T.S.; Aziz, S. Abd
The operation of the reservoir is a volume balance process amongst the inflows, storages and releases. Based on this principle, a simulation model (SM) for the Mosul reservoir was formulated of using the Simulink® technique in the MATLAB® environment. In order to test the accuracy of this model, two performance evaluation criteria (r² and NSE) were adopted by comparing the observed elevations of storages and hydropower generated with the values resulted from the simulation model. The r² and NSE are 0.92 and 0.87 respectively in comparison of elevations, while they were 0.81 and 0.77 respectively in comparison of hydropower generated. The results showed that the model performance is promising to be used in real application. This work highlighted the advantages and flexibility of the Simulink technique in the formulation of the simulation model which pertains to the reservoirs operation in addition to the high speed in executing the simulation process.